Hubungan antara Lingkungan Sosial dengan Harga Diri Remaja Panti Asuhan Al Jam’iyatul Washliyah Binjai - Syafrizaldi Syafrizaldi; Shafira Pratiwi (Mahesa Research Center, 2020)
This study aims to find The Correlation between Social Environment and Self-Esteem on Teenagers at Al Jam’iyatul Washliyah Orphanage in Binjai. The subject were 56 teenagers who lived in the orphanage. The sample was collected by using total sampling technique. The data was collected by using social environment and self-esteem scales. The data was analyzed by using correlation technique (rxy) in the amount of 0,792 with p = 0,000 < 0,050 which means there was a positive and significant relationship between social environment and self-esteem, it showed that the better the social environment, the higher self-esteem. Conversely, the worse the environment, the lower self-esteem. Social environment in this study was classified as high, due to (empirical mean = 111,32 > hypothetical mean = 90 where the difference exceeds the numbers of SD = 13,087). Self-esteem was also classified as high, due to (empirical mean = 120,68 > hypothetical mean = 95 where the difference exceeds the numbers of SD = 13,051). Coefficient of determination and correlation was r2 = 0,627 which means the social environment contributed 62,7% to self-esteem. Based on this study, there were still 37,3% influence of the other factors which weren’t revealed in this study.